2003
DOI: 10.1038/sj.cgt.7700578
|View full text |Cite
|
Sign up to set email alerts
|

Replication of an integrin targeted conditionally replicating adenovirus on primary ovarian cancer spheroids

Abstract: Replication competent viruses hold promise for treatment of advanced cancers resistant to available therapeutic modalities. Although preliminary clinical results have substantiated their efficacy, preclinical development of these novel approaches is limited by assay substrates. The evaluation of candidate agents could be confounded by differences between primary tumor cells and tumor cell lines, as discordance in the levels of surface receptors relevant for viral entry has been reported. Since primary tumor ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…5 Therefore, we have developed three-dimensional aggregates or spheroids of unpassaged and purified ovarian cancer cells as a means for prolonging primary tumor cell viability. 15 Spheroids also provide a threedimensional in vitro model for replicative viral infection. 15 As viral penetration of solid tumor proceeds in three dimensions, conventional two-dimensional cell culture assays might produce data that poorly represent these in vivo events.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…5 Therefore, we have developed three-dimensional aggregates or spheroids of unpassaged and purified ovarian cancer cells as a means for prolonging primary tumor cell viability. 15 Spheroids also provide a threedimensional in vitro model for replicative viral infection. 15 As viral penetration of solid tumor proceeds in three dimensions, conventional two-dimensional cell culture assays might produce data that poorly represent these in vivo events.…”
Section: Introductionmentioning
confidence: 99%
“…15 Spheroids also provide a threedimensional in vitro model for replicative viral infection. 15 As viral penetration of solid tumor proceeds in three dimensions, conventional two-dimensional cell culture assays might produce data that poorly represent these in vivo events. Spheroids, however, are often greater than 1 mm in diameter 16 and therefore allow viral spread through a solid rather than planar substrate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…21,22,[35][36][37] Also, relatively good correlation has been seen between tumor cell lines grown two-dimensionally on plates or as three-dimensional spheroids. [38][39][40] With regard to breast cancer, this has not been studied previously. However, a recent report suggested that the level and location of CAR were different when the same breast cancer cells were grown on plates versus in a Figure 4 Noninvasive imaging of viable tumor cells following treatment with Ad5.pK7-D24.…”
Section: Discussionmentioning
confidence: 99%